Tổng hợp một số dẫn xuất exahydropyrazin-[1,2b]-isoquinolin - Cường, Vũ Đức; Chính, Phạm Thế; Tuyết Anh, Đặng Thị; Thắm, Phạm Văn; Thanh Vân, Quách Thị; Tuyến, Nguyễn Văn (Vietnam Journal of Chemistry, 2017)
Various hexahydropyrazine[1,2b]isoquinolines were synthesized as simplified saframycin analogues, this compound isolated from Streptomyces lavendulae, belong to a family of microbial fermentation products with a remarkable antiproliferative activity. Construction of this core proceeded through tetrahydroisoquinoline synthesis followed by acylation/alkylation of the tetrahydroisoquinoline nitrogen and subsequent ring closure using various aliphatic and aromatic amines. All these compounds can be considered as dimers of structurally less complex tetrahydroisoquinoline subunits. Synthesis of these kinds of simplified analogues has received little attention as most work focuses on total synthesis. Therefore, the synthesis of quinone type derivatives under their hydroquinone methyl ether form was envisaged. Keywords. Synthesis, hexahydropyrazine, isoquinoline, eteinascindein.